Screening of Efficient Antifreeze Agents to Prevent Low-Temperature Stress in Vines - Yali Zhang; Mengyao Han; Langjie Wu; Haoyu Wang; Yanying Liang; Xianhang Wang; Zhumei Xi (Agronomy)
Grapevines are widely cultivated and highly nutritious, making them economically significant among cultivated plants globally. However, important spring temperature fluctuations and frequent frost events in some production areas severely affect grape growth and yield. Therefore, enhancing the cold resistance of grapevines is of considerable importance for production. This study used the less cold-resistant grape varieties Vitis vinifera cv. Cabernet Sauvignon and Vitis vinifera cv. Chardonnay as test materials. They were treated with the antifreeze agents ‘GuoGuang KangXiu,’ ‘Biogas Liquid’, ‘SenHuo’, and ‘Ice Shield’ for 24 and 48 h before exposure to a low-temperature treatment of −2 °C. Compared to the control (water), all four antifreeze agents significantly reduced the relative conductivity and malondialdehyde content in the tender shoots of both grape varieties, increased the Fv/Fm ratio, enhanced osmotic adjustment substance levels, and improved antioxidant enzyme activity. Moreover, relative conductivity and malondialdehyde content were significantly lower, and the Fv/Fm ratio was higher when the antifreeze agents were applied 24 h before frost compared to 48 h. This suggests that all four antifreeze agents effectively improve grapevine cold resistance, with better results observed when applied 24 h before frost. Additionally, the antifreeze agents significantly increased the soluble solid content in berries and enhanced the levels of anthocyanins, total phenols, total tannins, total flavonoids, and total flavonols in the berries’ skin. They had minimal impact on the fruit set rate, cluster weight, and berries shape index, indicating that these agents can improve berries quality to some extent.